2003
DOI: 10.1063/1.1599039
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc superconducting quantum interference device observation of heat-affected zone in a spot-welded Fe–Cr–Ni system

Abstract: A study was carried out to observe a heat-affected zone (HAZ) in a deformed Fe–Cr–Ni system containing α′ martensite using high-Tc superconducting quantum interference device (SQUID) microscopy. Microstructure and remanent magnetization images were studied by an optical microscope and a SQUID microscope, respectively. The HAZ, in which only the face-centered-cubic austenite phase exists, could be visualized by the SQUID microscope. It was also found that the SQUID images were consistent with the results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, the specimen temperature should ideally be measured by many thermocouples attached to the specimen surface by spot welding. However, recently it was found that a heat affected zone (HAZ), 13 in which only the austenite phase exists, was produced in the deformed stainless steel by spot welding. To avoid unnecessary experimental error, therefore, a movable thermocouple was used to measure the thermal gradient within the specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the specimen temperature should ideally be measured by many thermocouples attached to the specimen surface by spot welding. However, recently it was found that a heat affected zone (HAZ), 13 in which only the austenite phase exists, was produced in the deformed stainless steel by spot welding. To avoid unnecessary experimental error, therefore, a movable thermocouple was used to measure the thermal gradient within the specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning SQUID microscopes are used to investigate the spatial distributions of magnetic fields on sample surfaces; a SQUID of small washer size is used as a magnetic field detector [1][2][3][4]. It has been applied in various research areas, e.g., superconductivity, magnetism, material engineering, immunoassay, and nondestructive evaluation of metallic parts [5][6][7][8][9][10][11][12][13][14]. The efforts at enhancement of the spatial resolution otherwise limited by the SQUID loop size include the adoption of a small SQUID called a microSQUID [15], the laser excitation method [16], and the use of a flux-guiding needle [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis of the weld zone microstructure, optical microscope (OM), electron microscope, X-ray diffraction techniques, Mössbauer analysis and a superconducting quantum interference device (SQUID) microscope have been widely used. [2][3][4][5] The a to g phase transformation occurring in the HAZ of AISI 1005 steel ((0.05C, 0.31Mn, 0.18Si, 0.11Ni, 0.10Cr; by mass percent) welds was studied by in situ spatially resolved X-ray diffraction (SRXRD) experiments. 5) Numerical study on the effect of electrode force in small-scale resistance spot welding was reported by Chang and Zhou.…”
Section: Introductionmentioning
confidence: 99%